Therapeutic strategies for sarcopenic obesity: a systematic review. Issue 1 (January 2021) - Poggiogalle, Eleonora; Parrinello, Edda; Barazzoni, Rocco; Busetto, Luca; Donini, Lorenzo M.
Abstract : Purpose of review: Tough plenty of literature investigated therapeutic options for body composition changes targeting elderly people, evidence concerning potential treatments of sarcopenic obesity as a unique condition is scarce. The aim of the present review was to summarize recent evidence regarding treatment of sarcopenic obesity in adult and older individuals. Recent findings: Exercise-based interventions were effective in ameliorating lean mass or sarcopenia-related indices and reducing total adiposity. Importantly, in one study, modifications of body composition were obtained in the absence of significant changes in body mass index. The majority of studies relied on resistance training, and all provided with beneficial effects in body composition. Conversely, effects in terms of muscle strength and functional ability were heterogeneous. Electrical acupuncture and whole-body electromyostimulation associated with nutritional supplementation resulted to be novel effective strategies in inducing body composition changes. Nonetheless, findings from nutritional supplementations are not conclusive, leading to conflicting results on strength and functional outcomes. Summary: Specific interventions could improve sarcopenic obesity, but overall significance is limited by scarcity of data and lack of uniformity in the definition of sarcopenic obesity itself. Further research should clarify optimal treatment options for sarcopenic obesity in age classes other than the geriatric population.